Assess the outcome of pre and postoperative bacterial culture in sinonasal polyposis cases under FESS - Sudheer, C. P.; Singh, T. Dinesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Sinonasal polyposis is multifactorial condition characterised by mucous membrane lesions in nose and paranasal sinuses. Pre and post-operative management of cases undergoing functional endoscopic sinus surgery (FESS) give ideal surgical outcome. This study designed to assess pre and postoperative bacterial profile in sinonasal polyposis cases undergoing Functional endoscopic sinus surgery. Methods: A total 100 cases ready for endonasal endoscopic surgery with chief complaints of sinonasal polyposis were recruited for the study. Pre and post-operative nasal swabs were collected from lateral wall, floor and area over the polyps. Sensitivity test was performed by using commonly available antibiotics i.e. ceftriaxone, erythromycin, ampicillin, gentamycin, ciprofloxacin, cephalexin, doxycycline and co-trimoxazole. Results: Pre-operative bacterial culture showed growth of Staphylococcus coagulase negative (CONS) in 32% cases, Staphylococcus aureus in 24%. Post-operative bacteria culture showed Staphylococcus coagulase negative (CONS) in 22% cases, Staphylococcus aureus in 22% cases. Staphylococcus coagulase negative (CONS) and Staphylococcus aureus had resistance to Ampicillin and Gentamycin. Conclusions: Staphylococcus coagulase negative (CONS) and Staphylococcus aureus are isolated commonly in pre and post-operative bacteria culture. Ampicillin, gentamicin, cefotaxime and ceftriaxone are primary choice for intravenous antibiotics in current clinical practice and in al surgical procedures including endoscopic sinus procedures.